Pemberian Aroma Terapi Lemon dan Relaksasi Nafas Dalam dapat menurunkan tingkat stres ibu hamil - Firda, Alivia; Fitrianingtyas, Rizki; Sari, Melati Puspita (Politeknik Kesehatan Kemenkes malang, 2024)
Pregnancy stress is a state of pregnant women who are triggered by prejudice - bad prejudice that befalls her, if left unchecked it will have a negative impact on the mother and baby. Handling stress can be done with non-pharmacology in the form of giving lemon aromatherapy and deep breath relaxation. In PMB L there are first trimester pregnant women who experience pregnancy stress as many as 21 (65.6%) pregnant women out of 32 pregnant women. The purpose of this study was to determine the effect of lemon aromatherapy and deep breath relaxation on first trimester pregnant women at PMB L. This type of research is Pre-Experimental with a one Group Pretest-Posttest desing approach using Total Sampling. Data analysis using the Wilcoxond test with the result that the Asymp.Sig (2-tailed) value is <0.001. There is an effect of giving lemon aromatherapy and deep breath relaxation on the stress level of first trimester pregnant women at PMB L. Keywords: Lemon Aromatherapy, Deep Breath Relaxation, Stress of Pregnant WomenKeywords: Adolescents, Anemia, Date soy milk